Seasonal Variations in Soil and Plant Water Status in a Quercus suber L. Stand: Roots as Determinants of Tree Productivity and Survival in the Mediterranean-type Ecosystem - Otieno, D. O.; Kurz-Besson, C.; Liu, J.; Schmidt, M. W. T.; Do, R. Vale-Lobo; David, T. S.; Siegwolf, R.; Pereira, J. S.; Tenhunen, J. D. (Plant and Soil, 2006)
Studies were conducted to examine changes in soil (Ys) and plant water status during summer in a 16-year old Quercus suber plantation in southern Portugal. Continuous measurements were conducted between May 2003 and August 2004, while discontinuous measurements were conducted on a monthly basis between May and September 2003 and repeated between March and September 2004. Intensive measurements were conducted on ﬁve trees with mean height and DBH of 5.3 m and 11.6 cm, respectively, growing at close proximity to each other. Weather conditions and soil water potential (Ys) at the rhizosphere of each of the trees measured at 0.3 and 1 m soil depth were continuously monitored. Predawn (Ypd) and midday (Ymd) leaf water potentials were determined every month. Soil and plant samples were also collected in June and September from diﬀerent locations within the study site for d 18 O isotope composition analysis. Pressure–volume (p–v) curves were constructed from plant shoots at diﬀerent times during the vegetative period to determine osmotic potential at full saturation (P 100 ), water potential at turgor loss point (Ytlp), relative water content at turgor loss point (R*tlp) and bulk modulus of elasticity (e). Signiﬁcant P < 0.05 decline in Ys occurred between May and September, the lowest value recorded being –2.0 MPa. Decline in soil moisture aﬀected tree water status, but decline in leaf water potential varied signiﬁcantly (P < 0.05) among the trees. At the end of summer drought, lowest Ypd measured was –1.7 MPa while the highest measured during this time was –0.8 MPa. Diﬀerences among trees were attributed to diﬀerences in rooting depth, as shown by regression analysis of 18 O isotopes. Radial stem growth ceased when Ys within the upper 0.3 m depth approached –1.5 MPa. The upper soil layers contributed approximately 33% of the total tree water requirement, between spring and mid summer when drought was experienced by trees. Deep soil layers however, supplied most of the water required during drought and no growth was recorded during this time. Stressed trees increased solute concentration of their tissues by a Magnitude of 0.7 MPa while bulk tissue elastic modulus increased by about 17 MPa. The study emphasizes the signiﬁcance of roots as determinants of tree productivity and survival in the Mediterranean ecosystems.
Keywords: Drought stress; leaf water potential; osmotic adjustment; oxygen isotope; root distribution

Effects of temperature at constant air dew point on leaf carboxylation efficiency and CO 2 compensation point of different leaf types - Weber, J. A.; Tenhunen, J. D.; Lange, O. L. (Planta, 1985)
The effect of temperature on photosyn- thesis at constant water-vapor pressure in the air was investigated using two sclerophyll species, Ar- butus unedo and Quercus suber, and one meso- phytic species, Spinacia oleracea. Photosynthesis and transpiration were measured over a range of temperatures, 20-39 ~ C. The external concentra- tion of CO 2 was varied from 340 ~tbar to near CO 2 compensation. The initial slope (carboxylation effi- ciency, CE) of the photosynthetic response to inter- cellular CO 2 concentration, the CO 2 compensation point (/-), and the extrapolated rate of CO 2 re- leased into COa-free air (Ri) were calculated. At an external CO 2 concentration of 320-340 labar CO2, photosynthesis decreased with temperature in all species. The effect of temperature on F was similar in all species. While CE in S. oleracea changed little with temperature, CE decreased by 50% in Q. suber as temperature increased from 25 to 34 ~ C. Arbutus unedo also exhibited a de- crease in CE at higher temperatures but not as marked as Q. suber. The absolute value of Ri in- creased with temperature in S. oleracea, while changing little or decreasing in the sclerophylls. Variations in F and Ri of the sclerophyll species are not consistent with greater increase of respira- tion with temperature in the light in these species compared with S. oleracea.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature-humidity); Sclerophyll; Transpiration